2001
DOI: 10.1177/0146167201279008
|View full text |Cite
|
Sign up to set email alerts
|

Ostracism and Ego Depletion: The Strains of Silence

Abstract: Two studies examined whether ostracizing someone depletes psychological resources in the ostracizer. In Study 1, people who followed instructions to avoid conversation with a confederate for 3 minutes later showed decrements in persistence on unsolvable problems. In Study 2, ostracizers showed subsequent impairments in physical stamina on a handgrip task. Although ostracism affected mood too, mood did not appear to mediate the main findings. Past work has shown that ostracism has negative consequences for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
118
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 11 publications
6
118
3
Order By: Relevance
“…And as much recent work has shown (e.g., Twenge, Baumeister, Dewall, Ciarocco, & Bartels, 2007;Twenge and Baumeister, 2005) those who have been ostracized may become aggressive, uncooperative, or unmotivated (unlike those who have simply been threatened with social exclusion, contingent on their future behavior, like our participants). Moreover, there are a number of tangible costs to the group for using this means of social control-it can be as psychologically aversive to ostracize as it is to be ostracized (Ciarocco, Sommer, & Baumeister, 2001), monitoring compliance and excluding norm deviants can require a number of resources (potentially creating a second-order, enforcement dilemma, Kameda et al, 2003;Yamagishi, 1986). Still, the net costs to the group of using social exclusion may be far less than alternative methods of social control (e.g., fining defectors).…”
Section: Discussionmentioning
confidence: 99%
“…And as much recent work has shown (e.g., Twenge, Baumeister, Dewall, Ciarocco, & Bartels, 2007;Twenge and Baumeister, 2005) those who have been ostracized may become aggressive, uncooperative, or unmotivated (unlike those who have simply been threatened with social exclusion, contingent on their future behavior, like our participants). Moreover, there are a number of tangible costs to the group for using this means of social control-it can be as psychologically aversive to ostracize as it is to be ostracized (Ciarocco, Sommer, & Baumeister, 2001), monitoring compliance and excluding norm deviants can require a number of resources (potentially creating a second-order, enforcement dilemma, Kameda et al, 2003;Yamagishi, 1986). Still, the net costs to the group of using social exclusion may be far less than alternative methods of social control (e.g., fining defectors).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has established the profoundly negative emotional impact of ostracism on its targets (Eisenberger, Lieberman, & Williams, 2003;Williams, 2007;Baumeister & Leary, 1995), as well as on its sources (Ciarocco, Sommer, & Baumeister, 2001;Legate, De Haan, Weinstein, & Ryan, 2013;Poulson & Kashy, 2011;see Zadro & Gonsalkorale, 2014 for a review). Less understood are the cognitive im-plications of exclusion and, in particular, its impact on how interpersonal relationships are experienced and perceived.…”
Section: Just You and I: The Role Of Social Exclusion In The Formatiomentioning
confidence: 99%
“…They were instructed that, if they agreed to take part in the 'ignore' condition, they should completely ignore the Target participant and talk over them to the Ally to ensure that the Target felt truly ignored. This procedure was adapted from Ciarocco et al (2001) and was chosen to enhance ecological validity by ensuring that the Instigators felt that they had freely chosen to exclude the Target.…”
mentioning
confidence: 99%
“…Participants who avoided conversation with a confederate for 3 min showed reduced persistence on unsolvable problems later. Furthermore, avoiding conversation with others impaired the physical stamina for the ostracizer (Ciarocco et al, 2001). These results showed that ostracizing someone is a strenuous task that depletes self-control (Ciarocco et al, 2001).…”
mentioning
confidence: 91%
“…Previous studies examined the harmful impact on the ostracizer and found that ostracizing someone depletes psychological resources in the ostracizer (Ciarocco, Sommer, & Baumeister, 2001). Participants who avoided conversation with a confederate for 3 min showed reduced persistence on unsolvable problems later.…”
mentioning
confidence: 95%